COMPARISON OF PERCUTANEOUS NEPHROLITOTOMY (PCNL) IN PRONE AND SUPINE POSITION: A SINGLE CENTRE EXPERIENCE REPORT - Safriadi, Ferry; Ramdhan, Dadan (Indonesian Journal of Urology, 2021)
Objective: This study aims to compare outcomes of supine percutaneous nephrolithotomy to prone percutaneous nephrolithotomy as a traditional approach in Hasan Sadikin Hospital Bandung. Material & Methods: Data was taken from urology’s database between 2003-2012, which contain data of prone position (2003-2007), and supine position (2008-2012). Three hundred forty-nine patients were included in this study. We reviewed data on demography, stone burden, operating time, stone-free rate, transfusion rate, hospital stay, and major complications. Results: Of 174 patients underwent prone position, and 175 patients were part of the supine position. Age means of prone position was 51.0 years old, the supine position was 50.5 years old. The number of male patients was 65.5% for prone, and 66.1% for supine. The mean stone's largest diameter of prone was 23.87 mm, supine was 22.36 mm. The operating time of prone was 107 minutes; supine was 90 minutes. The stone-free rate of prone was 94.7%; supine was 91.3%. The mean hospital stays of prone was 14.3 days; supine was 9.6 days. The transfusion rate of prone position was 8.9%, supine was 7.2%. No major complications were recorded. Conclusion: Higher stone-free rates are achieved with patients in the prone position during PCNL. Supine position has shorter operating time, and hospital stay, lower blood transfusion rates. The complication rate is not different between the two positions.